"THE UNIQUE STRENGTHS OF C PROGRAMMING AND ITS DISTINCTION FROM OTHER LANGUAGES" (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
this article tax report and declarations in the 1c program preparation and reports in submission conveniences , precisions and other of programs auffazllillari and disadvantages based on analyses statement does . Software of supply other from programs and paper from documents differences and paperwork because of tax in the system to the surface arrived problems and to them solution as a result created program with general acquaintance about information is given .